The International Balance of Payments Role in the Economy of Indonesia - Astuti, Ismadiyanti P; Oktavilia, Shanty; Rahman, Agus Rubianto (Semarang State University, 2015)
The balance of payments is an indicator of economic fundamentals. Balance of payment describes the ability of a country to gain foreign exchange and foreign payments. This study aimed to analyze the determinants of the balance of payments on the Indonesian economy . It usedÂ Thirlwall and Hussain models and also Duasa empirical model. This study used secondary data years 1987-2014, namely foreign exchange reserves, exports, foreign investment, the exchange rate and the real gross national income. The results showed that the performance of the balance of payments in Indonesia can be explained by the models shown in accordance with the hypothesis, but on several variables did not show a significant correlation.